MULTIDIMENSIONAL ANALYSIS IN THE CREATION OF MEDICAL CLUSTERS IN ŁÓDŹ – A CONCEPTUAL WORK - Twaróg, Sebastian; Ojrzyńska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
This article aims at presenting a concept of the way entities that provide medical services should be selected for clusters. A medical cluster is a designated group of entities that represent complimentary competencies and are connected organisational, legal, financial and scientific interdependencies. A medical cluster is oriented to benefit from a synergy effect to support patients, the state budget and science. The research employed a multidimensional data analysis. Firstly, a hierarchical grouping procedure was used to distinguish groups of hospitals that have similar medical competencies. Then, division criteria that characterise competence differences within the groups in question were found. This way, groups of dissimilar (the most dissimilar) hospitals were obtained. Subsequently, on the basis of a minimal distance criterion, one entity was selected from each group to obtain new groups of entities that were decisively different in the context of medical services offered and simultaneously situated in the close vicinity to one another. These two aspects may offer some premises to initiate co-operation between the entities subject to the research within a given medical cluster.